Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/humu.23940
|View full text |Cite
|
Sign up to set email alerts
|

Long‐read nanopore sequencing resolves a TMEM231 gene conversion event causing Meckel–Gruber syndrome

Abstract: The diagnostic deployment of massively parallel short-read next-generation sequencing (NGS) has greatly improved genetic test availability, speed, and diagnostic yield, particularly for rare inherited disorders. Nonetheless, diagnostic approaches based on short-read sequencing have a poor ability to accurately detect gene conversion events. We report on the genetic analysis of a family in which 3 fetuses had clinical features consistent with the autosomal recessive disorder Meckel-Gruber syndrome (MKS). Target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…MKS is a much more deadly perinatal syndrome. As the severe part of the ciliopathy phenotypic spectrum, MKS-affected individuals present with polycystic kidneys, occipital encephalocele, and polydactyly ( 13 ). To date, mutations in more than 27 genes are associated with JBTS, and pathogenic variants in at least 17 genes have been identified in MKS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MKS is a much more deadly perinatal syndrome. As the severe part of the ciliopathy phenotypic spectrum, MKS-affected individuals present with polycystic kidneys, occipital encephalocele, and polydactyly ( 13 ). To date, mutations in more than 27 genes are associated with JBTS, and pathogenic variants in at least 17 genes have been identified in MKS patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, mutations in more than 27 genes are associated with JBTS, and pathogenic variants in at least 17 genes have been identified in MKS patients. Importantly, mutations in 12 of these genes, including TMEM231, TMEM67 , and TEME237, are reported to cause both conditions ( 13 , 14 ). As JBTS and MKS share overlapping features and are genetically heterogeneous, some laboratories routinely deploy a gene panel diagnostic approach that examines all JBTS- or MKS- associated disease genes, irrespective of which of the two diagnostic categories the clinical features suggest ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene conversion, defined as the replacement of a locus in the genome by a paralogous sequence, is a mechanism known to generate pathogenic alleles (Casola et al, 2012; Chen et al, 2007). For instance, a pathogenic converted allele has been described for the TMEM231 gene, causing autosomal recessive Joubert and Meckel‐Gruber syndromes (Maglic et al, 2016; Watson et al, 2020). Other examples include a benign conversion of 88–351 nucleotides of BRCA1 intron 2 (Tessereau et al, 2015) mediated by the same breakpoint sites leading to a 37 kbp‐long deletion of exon 1 and 2 of BRCA1 .…”
Section: Figurementioning
confidence: 99%
“…Disentangling the disease-causing variants through short NGS reads is frequently limited since SBDS shares 97% identity with SBDSP1 [21][22][23] . Yamada et al reported two SDS patients with compound heterozygous mutations in the SBDS gene (c.258+2T>C on one allele and c.183_184delinsCT together with c.201A>G on the other), validated by Sanger sequencing.…”
Section: Introductionmentioning
confidence: 99%